ANTIBACTERIAL AND ANTIACNE ACTIVITY OF n-HEXANE FRACTION OF ALFALFA HERB (Medicago sativa L.) ETHANOL EXTRACT IN VITRO AND ON RABBIT (Oryctolagus cuniculus) - Fithria, Risha Fillah; Safitri, Erika Indah; Khasanyzulaikhah, Kharista; Nurazisa, Nurazisa (CENDEKIA EKSAKTA, 2023)
Propionibacterium acnes (P. acnes) can cause inflammation of the polysebaceous glands and lead to acne. Flavonoids in alfalfa herb are thought to have antibacterial and antiinflammatory properties. Flavonoids can be absorbed into n-hexane solvents. This study aims to determine antibacterial activity of n-hexane fraction of alfalfa herb ethanol extract (nHFAH) against P. acnes in vitro, to calculate the total flavonoid levels in the fraction, and to determine antiacne activity of the fraction on rabbit. This study is an experimental study with post-test control group design. Extraction of alfalfa herb was done by maceration method using 70% ethanol and fractionated with n-hexane. Antibacterial activity test was carried out using disk diffusion with 5 series of concentrations (15%, 20%, 25%, 30% dan 35%), positive control (clindamycin 2 Âµg/disk) and negative control (DMSO 100%). Diameters of the inhibition area were analyzed statistically using a Kruskal Wallis test followed by Mann Withney test with 95% of confidence level. Rabbit back skin was shaved on 5 different areas (3x3 cm2/area). Induced with 0.2 mL of P. acnes suspension (3x109 CFU/mL) intradermal. Acne formed (24 hours) on all areas, then were treated with T1 (clindamycin 2%), T2 (DMSO 100%), T3 (nHFAH 20%), T4 (nHFAH 25%), T5 (nHFAH 30%). Erythema diameter reduction on day 9 was analyzed using one-way anova, continued by post hoc tukey with 95% of confidence level. Total nHFAH flavonoid levels were tested by colorimetric method using UVVis spectrophotometer at Î» 429.5 nm. The results showed that nHFAH has antibacterial activity against P. acnes with an average value of diameter of inhibition area for each concentration were 7.30; 7.49; 7.75; 7.92 and 8.24 mm. nHFAH exhibits antiacne activity with the percentage for each concentration were 67.01%; 77.84% and 85.84% respectively. Total nHFAH flavonoid levels were 6.09 mgQE/ gram.Keywords: Alfafa herb, n-Hexane fraction, Propionibacterium acnes.